Why is money important in Jean-Baptiste Say's analysis?. Issue 1 (2nd January 2017) - Jacoud, Gilles
Abstract: Jean-Baptiste Say dedicated a significant part of his work to monetary questions, as much to explain the monetary practices of his period and to propose concrete measures to improve certain elements, as to develop theoretical reflections on the role of money in the mechanisms that political economy sheds light upon. His thought for that matter is not always devoid of contradictions when it comes to reconciling the results of observation with certain dimensions of his analysis. The article explains his conception of money. A variation in its quantity has an impact not only on prices, but also on the real economy, favourable when this issue is slow and moderate, but negative, on the other hand, when it is fast and large-scale. This leads to the measures of monetary policy recommended by Say.